Evaluation of Two PET Bottles Caps: An Exploratory Study - Silva, Danilo C. [UNESP]; Bonfim, Gabriel H.C. [UNESP]; Paschoarelli, Luis C. [UNESP]; Fabio, Deborah R. [UNESP]; Alves, Ana L. [UNESP]; Merino, Eugênio A.D.; Merino, Giselle S.A.D.; Garcia, Lucas J. (Elsevier, 2015)
Packaging design is a key factor on the use of the products. For packagings that require the application of biomechanical forces, some features may favor or hinder the user's ability to open them. In soft drink PET packaging, the cap features play an important role in the application of forces and perception of the activity. The aim of this study is to evaluate two models of PET bottle caps widely used in Brazil. The study variables are the torque force exertion and thermal images of the hands of the subjects before and after the attempts of opening. This study has an exploratory and experimental character and included 16 subjects of both genders. The materials include one single PET packaging model properly adapted for the purpose of the study; two cap models with different characteristics; a torque transducer; and a digital thermograph. Data was analyzed using descriptive statistics and tests for mean comparisons. The results point out that the cap design may have influenced the opening forces applied, but not the temperatures measured at the evaluated points on the subject's hands.
Keywords: design; ergonomics; packaging; PET bottle.; thermography